2020
DOI: 10.1186/s13287-020-01925-y
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood-derived monocytes show neuronal properties and integration in immune-deficient rd1 mouse model upon phenotypic differentiation and induction with retinal growth factors

Abstract: Background Cell therapy is one of the most promising therapeutic interventions for retinitis pigmentosa. In the current study, we aimed to assess if peripheral blood-derived monocytes which are highly abundant and accessible could be utilized as a potential candidate for phenotypic differentiation into neuron-like cells. Methods The peripheral blood-derived monocytes were reconditioned phenotypically using extrinsic growth factors to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…NOD.SCID-rd1 mouse, developed in NII, New Delhi [ 15 , 22 ], is a double knockout model ( PDE6B−/− PRKDC−/− ) that mimics RP with slow-progressing photoreceptor degeneration. The model is bereft of photoreceptors by P28 and does not have functional adaptive immunity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NOD.SCID-rd1 mouse, developed in NII, New Delhi [ 15 , 22 ], is a double knockout model ( PDE6B−/− PRKDC−/− ) that mimics RP with slow-progressing photoreceptor degeneration. The model is bereft of photoreceptors by P28 and does not have functional adaptive immunity.…”
Section: Resultsmentioning
confidence: 99%
“…Neuroprotection and photoreceptor rescue through transplanted photoreceptor progenitors/precursors cells have been shown in the rd1 mouse and Gnat −/− mouse model of night blindness [ 34 , 42 ]. Very recently, our collaborators demonstrated that peripheral blood-derived monocytes show neuronal properties and integration in immune-deficient rd1 mouse model upon phenotypic differentiation and induction with retinal growth factors [ 22 ]. Previously, they reported that while BALB/c displayed an intact retina, CBA/J and NOD.SCID-rd1 lost their outer segment (rod cells) of the photoreceptor layer and ONL in 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…While one team did not [ 126 ], several independent laboratories, including ours, encountered that a subpopulation of monocytes can proliferate under certain culture conditions. [ 114 116 , 123 , 127 ] We only found a small degree of replication, which in our hands, limits the expandability of pluripotent monocytes [ 114 ]. In contrast, Zhao and colleagues were able to expand and store these cells for future experiments [ 115 ].…”
Section: Introductionmentioning
confidence: 90%
“…In contrast, Zhao and colleagues were able to expand and store these cells for future experiments [ 115 ]. Results from Mishra et al suggest replication in pluripotent monocytes is only temporary, peaking at day 6 and abating by day 10 [ 127 ]. These discrepancies in replication rates could be explained by methodological differences in generating pluripotent monocytes.…”
Section: Introductionmentioning
confidence: 99%
“…We transplanted iTregs in the sub-conjunctiva, leading to a sustained release of TGF-Β1 into the retina of 4 weeks old rd1 in-vitro-generated Retinal Neuron Like Cells (RNLCs) as cell therapy in the study [32]. These RNLCs were generated from blood monocytes in a two-step culture procedure and shown to be functionally similar to retinal cells including photoreceptors and can rescue vision perception in the rd1 model [32]. We then evaluated whether the adjunct TGF-Β1 treatment could improve the survival of cell therapy and hence rescue vision in the rd1mouse model.…”
Section: Introductionmentioning
confidence: 99%